Zapuščina zapisovalca ljudskih pesmi Gabriela Majcna - Muršič, Rajko (Traditiones (Ljubljana), 2005)
While studying the local alternative rock scene in the village of Trate in theregion of Slovenske Gorice, the author came across the century-old documents and records of a collector of folk songs, Gabriel Majcen, who was born in the mid- 19th century in the neighboring village of Zgornja Velka. In addition to more that 1000 transcriptions of folk songs with melodies, a very important discovery was Majcen's manuscript with an ethnographic questionnairefrom 1907-1908, wich had never been published because the well-known Slavic scholar Karel Štrekelj had rejected it. The autor discusses various similarities and differences in the status of an intellectual doing fieldwork in the same location, albeit a century later. The standardization and nationalization of folk song in the late 19th century and the radically changed research agenda in the 21st century is emphasized. However, the lowestcommon denominator remains the permanent financial problems that field researshers must deal with.
Keywords: Majcen, Gabriel, 1858-19??; ethnology; etnologija; folkloristics; folkloristika; slovenske ljudske pesmi; Slovenske gorice; zapuščine; zgodovinski pregledi